2002
DOI: 10.1016/s0168-1923(02)00104-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental controls over carbon dioxide and water vapor exchange of terrestrial vegetation

Abstract: Bakwin, P.; Berbigier, P.; Davis, K.; Dolman, A. J.; Falk, M.; Fuentes, J. D.; Goldstein, A.; Granier, A.; Grelle, A.; Hollinger, D.; Janssens, I. A.; Jarvis, P.; Jensen, N. O.; Katul, G.; Mahli, K.; Matteucci, G.; Meyers, T.; Monson, R.; Munger, W.; Oechel, W.; Olson, R.; Pilegaard, K.; Paw U, K. T.; Thorgeirsson, H.; Valentini, R.; Verma, Shashi; Vesala, T.; Wilson, K.; and Wofsy, S., "Environmental controls over carbon dioxide and water vapor exchange of terrestrial vegetation" (2002 B.E. Law et al. / Agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

76
798
7
18

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,199 publications
(899 citation statements)
references
References 81 publications
76
798
7
18
Order By: Relevance
“…One therefore has to limit model validation to interannual and seasonal variations of carbon stocks and fluxes using the model at equilibrium. This was also done here, yet it is well established that most FluxNet sites are net carbon sinks [e.g., Law et al, 2002]. Simulated half-hourly CO 2 fluxes were therefore corrected in order to account for these sinks.…”
Section: B3 Initialization Of the Modelmentioning
confidence: 99%
“…One therefore has to limit model validation to interannual and seasonal variations of carbon stocks and fluxes using the model at equilibrium. This was also done here, yet it is well established that most FluxNet sites are net carbon sinks [e.g., Law et al, 2002]. Simulated half-hourly CO 2 fluxes were therefore corrected in order to account for these sinks.…”
Section: B3 Initialization Of the Modelmentioning
confidence: 99%
“…Previous studies have demonstrated that the spatial variation in LAI could affect the spatial patterns of different components of AET. For example, evaporation of canopy interception depended on LAI (Jung et al, 2011), and the proportion of AET that evaporated from soil surfaces increased as LAI decreased (Law et al, 2002). Thus, it is seemly that LAI regulates the spatial patterns of AET mainly by influencing the proportion of different AET components (i.e., vegetation transpiration, soil evaporation and evaporation of canopy interception).…”
Section: Effects Of Climate and Vegetation On The Spatial Variation Imentioning
confidence: 99%
“…Given the pronounced covariation or interactive effects among climatic factors (e.g., MAT vs. R n , MAT vs, VPD, MAP vs. RH) and vegetation attributes (e.g., MAT vs. LAI, MAP vs. LAI) (Law et al, 2002), it is not surprised that the spatial patterns of AET significantly correlated with that of R n , VPD, RH and LAI. To better understand the climate and vegetation controls on the spatial variation in AET, it is important to comprehensively understand the roles of different potential influencing factors, especially vegetation attributes, in regulating the spatial patterns of AET.…”
Section: Effects Of Climate and Vegetation On The Spatial Variation Imentioning
confidence: 99%
“…Here, we use over 40 site-years of data from the AmeriFlux network (Law et al, 2002) to examine forest, crop, and grassland albedo parameterizations of several LSMs and use inverse methods to suggest several improved parameterizations. This is a far more comprehensive dataset than used in previous estimates of albedo, providing continuous replication within functional types and across years.…”
Section: Introductionmentioning
confidence: 99%